A Biomarker Panel (Bioscore) Incorporating Monocytic Surface and Soluble TREM-1 Has High Discriminative Value for Ventilator-Associated Pneumonia: A Prospective Observational Study - Grover, Vimal (Public Library of Science, 2014)
INTRODUCTION: Ventilator-associated pneumonia (VAP) increases mortality in critical illness. However, clinical diagnostic uncertainty persists. We hypothesised that measuring cell-surface and soluble inflammatory markers, incorporating Triggering Receptor Expressed by Myeloid cells (TREM)-1, would improve diagnostic accuracy. METHODS: A single centre prospective observational study, set in a University Hospital medical-surgical intensive Care unit, recruited 91 patients into 3 groups: 27 patients with VAP, 33 ventilated controls without evidence of pulmonary sepsis (non-VAP), and 31 non-ventilated controls (NVC), without clinical infection, attending for bronchoscopy. Paired samples of Bronchiolo-alveolar lavage fluid (BALF) and blood from each subject were analysed for putative biomarkers of infection: Cellular (TREM-1, CD11b and CD62L) and soluble (IL-1β, IL-6, IL-8, sTREM-1, Procalcitonin). Expression of cellular markers on monocytes and neutrophils were measured by flow cytometry. Soluble inflammatory markers were determined by ELISA. A biomarker panel (‘Bioscore’), was constructed, tested and validated, using Fisher’s discriminant function analysis, to assess its value in distinguishing VAP from non VAP. RESULTS: The expression of TREM-1 on monocytes (mTREM-1) and neutrophils (nTREM-1) and concentrations of IL-1β, IL-8, and sTREM-1 in BALF were significantly higher in VAP compared with non-VAP and NVC (p<0.001). The BALF/blood mTREM-1 was significantly higher in VAP patients compared to non-VAP and NVC (0.8 v 0.4 v 0.3 p<0.001). A seven marker Bioscore (BALF/blood ratio mTREM-1 and mCD11b, BALF sTREM-1, IL-8 and IL-1β, and serum CRP and IL-6) correctly identified 88.9% of VAP cases and 100% of non-VAP cases. CONCLUSION: A 7-marker bioscore, incorporating cellular and soluble TREM-1, accurately discriminates VAP from non-pulmonary infection.